3D Printing of Bioinspired Liquid Superrepellent Structures. Issue 22 (30th March 2018) - Liu, Xiaojiang; Gu, Hongcheng; Wang, Min; Du, Xin; Gao, Bingbing; Elbaz, Abdelrahman; Sun, Liangdong; Liao, Julong; Xiao, Pengfeng; Gu, Zhongze
Abstract: Bioinspired re‐entrant structures have been proved to be effective in achieving liquid superrepellence (including anti‐penetration, anti‐adhesion, and anti‐spreading). However, except for a few reports relying on isotropic etching of silicon wafers, most fluorination‐dependent surfaces are still unable to repel liquids with extreme low surface energy (i.e., γ < 15 mN m −1 ), especially those fluorinated solvents. Herein, triply re‐entrant structures, possessing superrepellence to water (with surface tension γ of 72.8 mN m −1 ) and various organic liquids (γ = 12.0–27.1 mN m −1 ), are fabricated via two‐photon polymerization based 3D printing technology. Such structures can be constructed both on rigid and flexible substrates, and the liquid superrepellent properties can be kept even after oxygen plasma treatment. Based on the prepared triply re‐entrant structures, micro open capillaries are constructed on them to realize directional liquid spreading, which may be applied in microfluidic platforms and lab‐on‐a‐chip applications. The fabricated arrays can also find potential applications in electronic devices, gas sensors, microchemical/physical reactors, high‐throughput biological sensors, and optical displays. Abstract : Triply re‐entrant structures with superrepellence to various liquids (12.0–72.8 mN m −1 ) are fabricated via two‐photon‐polymerization‐based 3D printing technology. Such liquid structures can be constructed both on rigid and flexible substrates. By constructing two parallel walls on the top of the triply re‐entrant array, directional liquid flow toward various wettable liquids can be sucessfully realized.